A Case Report: Vesico Vaginal Fistula - Yulia Margaretta Sari`; Rezi Amalia (Universitas Andalas, 2022)
Background: Vesica vaginal fistula is a part of urogenital fistula wich condition that present fistula between bladder and vagina and make urine mold through vagina. Case Report: Nullipara woman, 48 years old, admitted with complaining mold of urine from vagina since ten months ago after seven days having surgery procedure. Complaint appeared seven days after hysterctomi procedure as indication of uterine myoma. The vital signs are normal. On Per Speculum examination, clearly see there are fluids on the posterior fornix. Methylene blue test show result one fistula is at the top anterior of vagina, 6 cm proximal from hymenal ring about 1-1.5 cm. The patient underwent fistulorraphy with a vaginal approach using the futh mayo technique Discussion: Vesica vaginal fistula usually occur in the development country. Predisposition factors of it caused by hysterectomy procedure, besides trauma during labor and complications of pelvic surgery may also too. Physical and additional specific examination conventionally or minimally invasive like cystoscopy, cystography with contrast can obtain diagnosis, determine the location, size and number of fistula. Surgery is the mainstay therapy for urogenital fistula through trans vaginal or trans abdomen. Approaching depends on knowledge, experience and collaboration with other experts if needed. Surgery is the mainstay therapy for urogenital fistula through trans vaginal or trans abdomen. Approaching depends on knowledge, experience and collaboration with other experts if needed. Surgery is the mainstay therapy for urogenital fistula through trans vaginal or trans abdomen. Approaching depends on knowledge, experience and collaboration with other experts if needed.